2011
DOI: 10.1007/s10508-011-9764-y
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Semantic Categorization

Abstract: Sex differences in certain cognitive abilities, including aspects of semantic processing, are well established. However, there have been no reports investigating a sex difference in semantic categorization. A total of 55 men and 58 women each judged 25 exemplars of natural categories (e.g., FRUITS) and 25 of artifact categories (e.g., TOOLS) as a nonmember, partial member, or full member of the given category. Participants also rated confidence for each judgment. Women provided a greater number vague (partial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…It is important that the effect of sex on verbal memory performance is not overlooked, as many previous studies have demonstrated superior verbal memory abilities in females when compared to males (e.g., Kramer et al, 2003; Lewin et al, 2001). Additionally, previous studies have also shown sex differences in semantic categorization, which our semantically-cued memory test is reliant upon (Pasterski, Zwierzynska, & Estes, 2011). Therefore, we determined that sex should be a covariate when examining behavioral performance.…”
Section: Discussionmentioning
confidence: 68%
“…It is important that the effect of sex on verbal memory performance is not overlooked, as many previous studies have demonstrated superior verbal memory abilities in females when compared to males (e.g., Kramer et al, 2003; Lewin et al, 2001). Additionally, previous studies have also shown sex differences in semantic categorization, which our semantically-cued memory test is reliant upon (Pasterski, Zwierzynska, & Estes, 2011). Therefore, we determined that sex should be a covariate when examining behavioral performance.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, because confidence is gauged before the judgment is made (Baranski & Petrusic, 1998), it may affect that judgment (Petrusic & Baranski, 2003). Indeed, confidence has been shown to predict performance on other cognitive tasks, such as mathematical problem solving (Casey, Nuttall, & Pezaris, 1997;Schmader et al, 2009) and semantic categorization (Estes, 2004;Pasterski, Zwierzynska, & Estes, 2011). So given these sex differences in confidence and mental rotation, and given that confidence mediates performance on some cognitive tasks, confidence might mediate the sex difference in mental rotation.…”
Section: Confidence As a Potential Mediatormentioning
confidence: 99%